2017
DOI: 10.1159/000480337
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Lncrna MALAT1 Attenuates Neuronal Cell Death Through Suppressing Beclin1-Dependent Autophagy by Regulating Mir-30a in Cerebral Ischemic Stroke

et al.

Abstract: Background/Aims: LncRNA metastasis associated lung adenocarcinoma transcript 1 (MALAT1) was reported to be highly expressed in an in vitro mimic of ischemic stroke conditions. However, the exact biological role of MALAT1 and its underlying mechanism in ischemic stroke remain to be elucidated. Methods: The roles of MALAT1 and miR-30a on cell death and infarct volume and autophagy were evaluated in experimental ischemic stroke. The relationships between miR-30a and MALAT1, Beclin1 were confirmed by luciferase re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 41 publications
8
103
1
2
Order By: Relevance
“…Up regulated MALAT1 expression is correlated with poor overall survival in various cancers [4,22]. We found that its expression was up regulated in stroke tissues in our study in accordance with results from Guo et al [23]. Furthermore, we demonstrated that down regulation of MALAT1 suppresses ischemic injury both in vitro and in vivo, further attenuating neuronal cell death in cerebral ischemic stroke.…”
Section: Discussionsupporting
confidence: 91%
“…Up regulated MALAT1 expression is correlated with poor overall survival in various cancers [4,22]. We found that its expression was up regulated in stroke tissues in our study in accordance with results from Guo et al [23]. Furthermore, we demonstrated that down regulation of MALAT1 suppresses ischemic injury both in vitro and in vivo, further attenuating neuronal cell death in cerebral ischemic stroke.…”
Section: Discussionsupporting
confidence: 91%
“…Since apoptosis and autophagy are now relatively well defined mechanisms of stroke mediated brain injury [25,26], readily available compounds that are able to combat these pathways are desirable subjects of further studies to develop therapeutic strategies to treat stroke patients. In this study, we subjected rats to transient MCAO and studied the effects of bilobalide in post MCAO recovery.…”
Section: Discussionmentioning
confidence: 99%
“…After ische­mic stroke, it regulates gene expression in cerebrovascular endothelial cells [21, 22], where it is proposed to protect against hypoxia-reperfusion-induced apoptosis [23]. MALAT1 has been of interest as a therapeutic target after its downregulation was found to suppress ischemic injury and autophagy in vitro and in vivo, which makes its strong upregulation in our data of particular interest [24]. …”
Section: Discussionmentioning
confidence: 99%